An improvement model to optimise hospital interdisciplinary learning. Issue 5 (13th June 2016) - McNamara, Deborah A.; Rafferty, Paul; Fitzpatrick, Fidelma
Abstract : Purpose: – Interdisciplinary healthcare education and collaboration facilitates healthcare quality improvement (QI). Education challenges include cost, logistics and defining the optimum staff-engaging method. The purpose of this paper is to determine the optimum QI educational model and measure its impact using plan-do-study-act (PDSA) cycles. Design/methodology/approach: – The authors established an on-site interdisciplinary QI learning collaborative: weekly 30-minute learning sessions close to the working environment; a learning materials Twitter repository; and junior doctor-led QI work streams aligned with surgical directorate quality goals supported by a mentorship network. Delivery style (lectures, workshops and QI project reporting) and learning session content was planned weekly using PDSA cycles and modified using participant feedback (score 0-10). All surgical directorate QI work streams were measured before and at nine months. Findings: – From May 2014 to February 2015, there were 32 learning sessions with 266 scores (median 12 weekly, range 5-21). Workshop delivery scored the highest (mean score 9.0), followed by live project reports (mean score 8.8). The surgical QI work streams increased threefold from four to 12, including six junior doctor-led projects. Practical implications: – By proactively acting upon feedback, the authors centralised QI measurement and tailored learning sessions to staff needs. Building sustainability involves continually refining learning curriculum and QI work streams, and expanding the mentorship network. Originality/value: – The collaborative was established at no additional cost. Twitter is used to promote meetings, facilitate conversations and act as a learning repository. The mentorship framework builds QI and coaching expertise.